Der Kapitalismus entdeckt das Volk. Wie die deutschen Großbanken in den 1950er und 1960er Jahren zu ihrer privaten Kundschaft kamen - Gonser, Simon (Schriftenreihe der Vierteljahrshefte für Zeitgeschichte, 2014)
For a long time, big banks had little interest in having workers or employees as their customers. Only in the aftermath of the German Economic Miracle did Deutsche Bank, Dresdner Bank, and Commerzbank begin wooing the common people and their savings with new financial products. But were the big banks the real driving forces behind this change or were the banks being impelled by the dawn of a new dynamic epoch?